Performances of PMMA-based optical fiber bragg grating sensor in extended temperature range - Zhang, Wei; Webb, David J. (MDPI, 2021)
PMMA based optical fiber Bragg grating (POFBG) sensors are investigated in an environmental chamber with controlled temperature and relative humidity at temperature extended to 70 °C. At below a critical temperature of 50 °C the POFBG sensor exhibits good linearity and sensitivity for both temperature and humidity sensing. Nonlinear responses are observed at higher temperature, giving rise to varying, reduced magnitudes of sensitivities. An important feature of POFBG humidity sensing is observed at above critical temperature where the POFBG humidity sensitivity turns from positive to negative. A theoretical model based on Lorentz–Lorenz equation is presented to estimate the dependence of POFBG refractive index on temperature and relative humidity. The experimental results qualitatively agree with the theoretical analyses
Keywords: refractive index humidity dependence; thermo-optic effect; polymer optical fiber; fiber Bragg gratings